2010
DOI: 10.1152/jn.00671.2009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diabetes Increases Small Conductance Ca2+-Activated K+(SK) Currents That Alter Action Potential Properties and Excitability of Cardiac Motoneurons in the Nucleus Ambiguus

Abstract: Harden SW, Cheng ZJ. Maternal diabetes increases small conductance Ca 2ϩ -activated K ϩ (SK) currents that alter action potential properties and excitability of cardiac motoneurons in the nucleus ambiguus. J Neurophysiol 104: 2125-2138, 2010. First published July 28, 2010 doi:10.1152/jn.00671.2009. Parasympathetic cardiac motoneurons (PCMNs) in the nucleus ambiguus (NA) play a key role in regulating cardiac functions. In this study, we examined the effects of maternal diabetes on excitability, action potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
7
1
Order By: Relevance
“…As shown in Zheng et al (56), the blood glucose levels of normal FVB control mice were Ͻ 180 mg/dl. In addition, as shown in the previous study (27), the variations of blood glucose levels in the range of 131.9 -197.3 mg/dl between groups did not affect spike frequency and outward currents of PCMNs. Therefore, we consider that the neonatal FVB and NMDM mice used in the present experiments were all within the normal blood glucose range.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…As shown in Zheng et al (56), the blood glucose levels of normal FVB control mice were Ͻ 180 mg/dl. In addition, as shown in the previous study (27), the variations of blood glucose levels in the range of 131.9 -197.3 mg/dl between groups did not affect spike frequency and outward currents of PCMNs. Therefore, we consider that the neonatal FVB and NMDM mice used in the present experiments were all within the normal blood glucose range.…”
Section: Resultssupporting
confidence: 79%
“…Previously, we demonstrated that in the NA of neonatal mice, maternal diabetes reduced the excitability and increased their SK currents of PCMNs (27). In addition, blockade of SK channels with apamin substantially increased PCMN firing rate and completely abolished the difference of firing-rate between control and NMDM, indicating that SK channels significantly contribute to the reduction of excitability of PCMNs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, we have studied the effect of maternal diabetes on the PCMNs in neonatal mice. We found that in contrast to other models mentioned above, SK outward currents and tail currents of PNCMs are increased in neonates from diabetic mothers and are associated with reduced excitability of PNCMs (34). Previously, we have found that chronic intermittent hypoxia and diabetes may impair baroreflex function, induce NA motoneuron death, and alter NA control over the heart rate (22, 23, 32, 36, 37, 68 -70).…”
Section: Discussionmentioning
confidence: 57%
“…When the animals were not responsive to tail and toe pinch, a right thoracotomy was performed and the fluorescent tracer X-rhodamine-5 (and 6)-isothiocyanate (XRITC, 2%, 4 l; Molecular Probes, Eugene, OR) was injected into the pericardial sac at the base of the heart to retrogradely label cardiac motoneurons in the NA (25,37). Previously, XRITC has been used to label NA neurons for patch-clamp study of PCMNs (25,46,71).…”
Section: Fluorescent Labeling Of Pcmns and Brainstem Slice Preparatiomentioning
confidence: 99%